Aerosol Characterization at the Pierre Auger Obsrevatory - Micheletti, Maria Isabel (2013)
The Pierre Auger Observatory is a hybrid facility composed of surface and fluorescence detectors (denoted as SD and FD, respectively), where the FD system sets the energy scale in cosmic ray shower reconstruction. Atmospheric components attenuate the fluorescence light emitted by the de-excitation of atmospheric nitrogen, previously excited by the charged particles of the shower. Amongst these components, atmospheric aerosols are the ones with the largest fluctuations, being responsible for one of the major uncertainties in shower reconstruction with FD data. We present a detailed characterization of aerosols. They are collected at the Observatory and analyzed, in morphology and elemental composition, with experimental techniques used for the first time in a cosmic ray observatory: gravimetry, PIXE and SEM/EDX. An analysis of wind trajectories using the program HYSPLIT is used to understand the sources and the evolution of aerosols. The aerosols are further characterized by the FRAM, an optical telescope employed to perform CCD photometry of selected Landolt fields, in which we observe sets of precisely measured standard stars at various wavelengths. Using this photometric information we then compute the Angstr ˚ om coefficients that also characterize the size of aerosols.